Modeling in Event-B : system and software engineering - Abrial, Jean-Raymond (Cambridge : Cambridge University Press, 2010)
'A practical text suitable for an introductory or advanced course in formal methods, this book presents a mathematical approach to modeling and designing systems using an extension of the B formalism: Event-B. Based on the idea of refinement, the author's systematic approach allows the user to construct models gradually and to facilitate a systematic reasoning method by means of proofs. Readers will learn how to build models of programs and, more generally, discrete systems, but this is all done with practice in mind. The numerous examples provided arise from various sources of computer system developments, including sequential programs, concurrent programs, and electronic circuits. The book also contains a large number of exercises and projects ranging in difficulty. Each of the examples included in the book has been proved using the Rodin Platform tool set, which is available free for download at www.event-b.org'--Provided by publisher
Includes bibliographical references and index
Keywords: Formal methods (Computer science); B method (Computer science); Computer science -- Mathematical models; Computer systems -- Verification